2019
DOI: 10.18203/2320-1770.ijrcog20193046
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of polycystic ovary syndrome among women in reproductive age group attending a tertiary health care hospital in Western Maharashtra

Abstract: Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder affecting women of reproductive age group. Though its incidence is markedly increasing, the awareness is still low; as a result it remains undiagnosed. Aim of this study was to find the incidence and risk factors of PCOS among women in reproductive age group, so as to encourage young women to seek timely treatment and prevent its long term complications.Methods: A study was conducted over a period of 1 year amongst 100 women attending the Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The relation between obesity and PCOS is supported by the fact that a lifestyle change and control of weight will decrease PCOS symptoms and correct the hormonal imbalance. Two studies in India concluded that obesity increases the risk of PCOS to a lesser degree; it was seen that 40% of the overweight women suffered from PCOS 15,16 , and the same result (43%) in a study at a tertiary health care hospital in Western Maharashtra by Shinde, et al, (2019) 17 . In this study, the most common U/S finding was the bilateral presence of ≥12 follicles (2-9mm) (87.1%) followed by bilateral increased ovarian volume (>10m) (84.2%).…”
Section: Obstetrical History and Clinical Findingsmentioning
confidence: 76%
“…The relation between obesity and PCOS is supported by the fact that a lifestyle change and control of weight will decrease PCOS symptoms and correct the hormonal imbalance. Two studies in India concluded that obesity increases the risk of PCOS to a lesser degree; it was seen that 40% of the overweight women suffered from PCOS 15,16 , and the same result (43%) in a study at a tertiary health care hospital in Western Maharashtra by Shinde, et al, (2019) 17 . In this study, the most common U/S finding was the bilateral presence of ≥12 follicles (2-9mm) (87.1%) followed by bilateral increased ovarian volume (>10m) (84.2%).…”
Section: Obstetrical History and Clinical Findingsmentioning
confidence: 76%
“…To date, there have been no systematic studies available either globally or in India. In India, there are undersized, convenience-based studies reported, which might not reflect the true status of PCOS prevalence in the community [ 32 , 33 ]. It is difficult to draw a clear conclusion from this limited number of studies conducted across the country.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated, primarily to estimate the prevalence of PCOS in the country. Previously reported prevalence rates of PCOS have varied from 3.7% to 22.3% [ 32 , 33 ]. For the purpose of calculation of sample size, we presume the prevalence of PCOS in India to be 10%.…”
Section: Methodological Steps and Study Designmentioning
confidence: 99%
“…While a qualitative inquiry into unmarried reproduce age groups has been ignored in the literature, especially in the multicultural Indian context. Although a few studies, such as ( Gupta et al., 2015 ; Shinde and Patil, 2019 ), have compared unmarried and married women populations with PCOS, such comparisons were limited to exploring differences in clinical characteristics, incident rates and risk assessments. Notably, the women with PCOS for both the aforementioned studies were primarily unmarried than married.…”
Section: Introductionmentioning
confidence: 99%